Does employee trust matter? Measuring the effect of work engagement on turnover intention in the banking sector - Nazaruddin Malik (Universitas Muhammadiyah Yogyakarta, Indonesia, 2023)
Research aims: This study examines the effect of work engagement on the turnover intention with employee trust as a mediating variable in the banking sector in Malang, IndonesiaDesign/Methodology/Approach: This study uses a quantitative approach with data collection methods using questionnaires that were distributed online and processed using Partial Least Square (PLS) using a 119 response data.Research findings: The findings of this study show that work engagement has a negative effect on turnover intention. Employee trust mediated the effect between work engagement and turnover intention.Theoretical contribution/Originality: This study examined the role of employee trust as a mediating variable. Employee trust plays a vital role in maintaining people’s engagement on an organization, affecting low workers' intention to quit from their jobs. The results of this study confirm Maslow's motivational theory if employees are more involved in work and feel fulfilled. Employees will feel comfortable and reduce the level of turnover intention.Practitioner/Policy implication: These findings suggested leaders encourage engagement programs to increase employee trust to reduce turnover intention.Research limitation/Implication: The study had limitations, such as the few samples used and the fact that only Malang's banking industry employees were included.